Vision stick: An intelligent assistive device to support soldier mobility in visually impaired conditions - Muthumanickam K; Logeshwaran V; Sanjay B; Simon Marshal I (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
The Vision Stick is an innovative assistive device designed to enhance the mobility and independence of visually impaired individuals by integrating AI-powered vision models and ultrasonic sensors into a traditional white cane. Visually impaired individuals face significant challenges in navigating their surroundings, often relying on conventional mobility aids that lack advanced environmental awareness. To address this, the Vision Stick operates in two modes: an online AI vision mode and an offline ultrasonic mode. In online mode, a camera and AI algorithms analyze the surroundings, providing real-time voice descriptions of obstacles, landmarks, and hazards, improving navigation and safety. In offline mode, an ultrasonic sensor detects nearby objects and provides audio feedback, ensuring uninterrupted guidance without internet access. The device retains the familiar structure of a white cane while incorporating lightweight embedded components for ease of use. By combining AI-driven environmental awareness with ultrasonic obstacle detection, the Vision Stick enhances safety, confidence, and autonomy for visually impaired individuals in diverse environments.